Endoscopic Evaluation in Children With End-Stage Liver Disease–Associated Portal Hypertension Awaiting Liver Transplant. Issue 3 (September 2016) - Ng, Nicholas Beng Hui; Karthik, Sivaramakrishnan Venkatesh; Aw, Marion Margaret; Quak, Seng Hock
ABSTRACT: Objectives: Routine oesophago-gastro-duodenoscopy (OGD) pre-liver transplantation (LT) for evaluation and management of gastrointestinal (GI) pathology, in particular GI varices secondary to portal hypertension, is common practice in adult LT programmes. There is no universal consensus for this practice in children. We report our endoscopic experience in children with end-stage liver disease (ESLD) pre-LT. Methods: Retrospective audit of LT database and review of OGD findings of patients who had undergone endoscopy preceding LT. Results: Of 69 patients with ESLD, 50 (72.4%) had pre-LT OGD, 37 of which were done electively, whereas the remaining 13 were event driven. Forty-eight (96%) patients who underwent OGD had abnormalities, in which 38 (76%) patients had varices and 23 (46%) had portal hypertensive gastropathy. Eleven (22%) patients required therapeutic intervention at initial OGD either with endoscopic variceal band ligation or endoscopic sclerotherapy. Compared with the group who underwent elective OGDs, the group who had event-driven OGDs had a significantly higher requirement for endoscopic intervention ( P  < 0.0001), occurrence of rebleeding ( P  < 0.029) and requirement for repeat OGDs ( P  = 0.014). There was no significant difference in terms of patient ( P  = 0.2746) or graft survival ( P  = 0.3192) between the 2 groups. Conclusions: The role of pre-LT OGDs in patients with ESLD associated with portal hypertension is possibly limited to control of bleeding during episodes of GI bleed, where the aim would be to stabilize the patient until eventual LT. Multicentre prospective studies are required to provide more evidence on the use of routine endoscopy for pre-LT assessment in children.